The Influence of Transformational Leadership, Career Path and Comunication Toward Employee Perfomance at Contruction Company Harkon Persada Sukoharjo - Rochmi Widayanti, Bagas A. Pradipta, Ida Aryati Dyah Purnomo Wulan & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Infrastructure growth can boost economic growth. It can be the opportunities forconstruction companies to gain more omset which is the companys goal. Humanresources become an important asset owned by the company to achieve corporategoals. The success of achieving company goals is influenced by employeeperformance. The components of transformational leadership, career path andcommunication are important in managing human resources that can affectemployee performance. The purpose of this study is determining transformationalleadership, career path and communication affect employee performance. Thisresearch was conducted at construction company CV. Harkon Persada, Sukoharjo.The population is 50 people. The sampling method used is a saturated samplingwhich means all populations are used as samples. The method of analysis is usingmultiple linear regression. The results of this study indicate that transformationalleadership and communication have a positive and significant impact on employeeperformance. The career path has a negative and significant impact on employeeperformance..Keyword: Transformational Leadership, Career Path, Communication And EmployeePerformance